2015
DOI: 10.1136/jclinpath-2015-203125
|View full text |Cite
|
Sign up to set email alerts
|

Serine-arginine protein kinase 1 (SRPK1), a determinant of angiogenesis, is upregulated in prostate cancer and correlates with disease stage and invasion

Abstract: Vascular endothelial growth factor (VEGF) undergoes alternative splicing to produce both proangiogenic and antiangiogenic isoforms. Preferential splicing of proangiogenic VEGF is determined by serine-arginine protein kinase 1 (SRPK1), which is upregulated in a number of cancers. In the present study, we aimed to investigate SRPK1 expression in prostate cancer (PCa) and its association with cancer progression. SRPK1 expression was assessed using immunohistochemistry of PCa tissue extracted from radical prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
4
29
0
Order By: Relevance
“…However, as SILAC approaches measure protein abundance by MS1 quantitation, they can result in lower overall protein coverage (50). Thus, a potential limitation to measuring kinase levels in heterogeneous tissues using the Q-MIBs approach is that we can only quantitate with high confidence those kinases that have a matching Mis-spliced gene targets following SPHINX31-treatment were enriched in VEGF pathways and angiogenesis, consistent with recent studies showing SRPK1 function has been shown to block splicing of VEGF 165a to VEGF 165b reducing angiogenesis in cells and tumor models (38).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, as SILAC approaches measure protein abundance by MS1 quantitation, they can result in lower overall protein coverage (50). Thus, a potential limitation to measuring kinase levels in heterogeneous tissues using the Q-MIBs approach is that we can only quantitate with high confidence those kinases that have a matching Mis-spliced gene targets following SPHINX31-treatment were enriched in VEGF pathways and angiogenesis, consistent with recent studies showing SRPK1 function has been shown to block splicing of VEGF 165a to VEGF 165b reducing angiogenesis in cells and tumor models (38).…”
Section: Discussionsupporting
confidence: 70%
“…6D). Consistent with these findings, inhibition of SRPK1 has been previously shown to block splicing of VEGF 165a to VEGF 165b impacting Vegf signaling and angiogenesis (38).…”
Section: Srpk1 Inhibition Promotes Alternative Splicing Impairing Sursupporting
confidence: 65%
See 1 more Smart Citation
“…Approach Followed (Testing on Histology Samples/Blood; Data Mining) Level Tested (mRNA; Protein) Clinical Significance Reference Lung data mining; histology samples mRNA; protein 鈫慡RPK1 was found in NSCLC and was associated with higher tumor stage and shorter survival [29] histology samples mRNA; protein 鈫慡RPK1 was found in NSCLC [30] data mining mRNA 鈫慡RPK1 was found in lung adenocarcinoma (a NSCLC histologic type) [31] Breast histology samples mRNA; protein 鈫慡RPK1 was found in breast cancer and was associated with higher tumor stage and shorter survival [32] histology samples; data mining mRNA; protein 鈫慡RPK1 was associated with shorter survival in breast cancer and metastatic disease to the lungs and brain [33] data mining mRNA 鈫慡RPK1 was associated with shorter survival in HER2-negative breast cancer patients treated with chemotherapy [34] histology samples protein 鈫慡RPK1 was found in breast cancer [35] histology samples protein 鈫慡RPK1 was found in breast cancer [22] histology samples protein 鈫慡RPK1 was found in breast cancer and was associated with higher tumor grade [36] Prostate histology samples protein 鈫慡RPK1 was found in prostate cancer and its precursor (PIN) [26] histology samples protein 鈫慡RPK1 was found in prostate cancer and was associated with higher stage [37] Colorectal histology samples protein 鈫慡RPK1 was found in colon cancer and its precursor (adenoma) [22] histology samples protein 鈫慡RPK1 was found in colon cancer and was associated with higher tumor grade [36] histology samples mRNA; protein 鈫慡RPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [38] histology samples mRNA; protein 鈫慡RPK1 was found in colorectal cancer and was associated with higher tumor stage and shorter survival [39] histology samples mRNA 鈫慡RPK1 was found in colorectal cancer and its precursor (adenoma) [31] histology samples protein 鈫慡RPK1 and p-AKT were found in colon cancer [40] Stomach data mining mRNA 鈫慡RPK1 was found in gastric cancer [31] histology samples protein 鈫慡RPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [41] histology samples protein 鈫慡RPK1 was found in gastric cancer [42] histology samples mRNA; protein 鈫慡RPK1 was found in gastric cancer and was associated with higher tumor stage and shorter survival [43] Liver histology samples mRNA; protein 鈫慡RPK1 was associated with higher stage and shorter survival; SRPK1 expression was inversely correlated with miR-1296 expression…”
Section: Cancer Type (Primary Location)mentioning
confidence: 99%
“…54,55 The lower availability results in alterations in AS of specific genes regulated by MBNL, which contribute to myotonic dystrophy pathogenesis. SRPK1, a kinase that phosphorylates SR-proteins (the class of splice factors mentioned above), is overexpressed in several cancers [56][57][58] and also in DenysDrash syndrome, associated renal failure, and increased incidence of Wilms tumors. 59 SRPK1 is a determinant of angiogenesis through modulation of VEGF-A splicing and its abnormal expression maintains a pathologic loop by promoting proangiogenic and propermeability VEGF-A isoforms.…”
Section: Splice Factors or Splicing-specific Kinases Are Deregulated mentioning
confidence: 99%